The portability of human capital and immigrant assimilation: evidence for Spain - Esteve Sanromá; Raúl Ramos (Institute for the Study of Labor (IZA), 2008)
The existing literature on immigrant assimilation has highlighted the imperfect portability of human capital acquired by immigrants in their country of origin (Chiswick, 1978; Friedberg, 2000). This would explain the low levels of assimilation upon arrival in the new country, as well as the wide initial earnings gap. Recent studies (Chiswick and Miller, 2007 or Green, Kler and Leeves, 2007, among others) have dealt with this issue from the perspective of over-education. This study analyses the portability of immigrants' human capital into the Spanish job market according to their geographic origin. It also aims to compare the most notable empirical regularities found in the aforementioned studies with the situation in Spain. The results obtained indicate differing degrees of the transferability of human capital depending on geographic origin, as transferability is greater for countries that are highly developed or have a similar culture or language and lower for developing countries and those with more distant cultures. The evidence is relatively disparate for the two components of human capital as although it is particularly clear for schooling, it is less so for experience. The results also confirm that in Spain immigrants suffer from over-education, in both incidence and intensity, implying a higher relative wage penalty and a greater negative impact on immigrants from the second group of countries. As an immigrant's stay in Spain advances, a process of assimilation does exist, except for Asians and, in some circumstances, those from Sub-Saharan Africa, though the pace is very slow.
urn:nbn:de:101:1-20080825264
Keywords: J61; 330; Immigration; over-education; wages; assimilation; Migranten; Humankapital; Lohnstruktur; Soziale Integration; Überqualifikation; Spanien